2020
DOI: 10.2196/17038
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of an Embodied Conversational Agent for Type 2 Diabetes Self-Management Education and Support via a Smartphone App: Mixed Methods Study

Abstract: Background Embodied conversational agents (ECAs) are increasingly used in health care apps; however, their acceptability in type 2 diabetes (T2D) self-management apps has not yet been investigated. Objective This study aimed to evaluate the acceptability of the ECA (Laura) used to deliver diabetes self-management education and support in the My Diabetes Coach (MDC) app. Methods A sequential mixed methods des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 40 publications
(60 reference statements)
0
61
0
Order By: Relevance
“…The MDC app incorporated interactive voice recognition and an embodied conversational agent, Laura , with human-like characteristics who used a very conversational style of speech to provide people with T2DM with personalized coaching and support on a range of essential diabetes self-management activities in their home environment. The process evaluation that received response from 66 out of 93 participants at 6 months showed that more than 80% of them considered Laura as a helpful, friendly and competent assistant and 72% described Laura as trustworthy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MDC app incorporated interactive voice recognition and an embodied conversational agent, Laura , with human-like characteristics who used a very conversational style of speech to provide people with T2DM with personalized coaching and support on a range of essential diabetes self-management activities in their home environment. The process evaluation that received response from 66 out of 93 participants at 6 months showed that more than 80% of them considered Laura as a helpful, friendly and competent assistant and 72% described Laura as trustworthy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complete list of included studies (26 studies) used CAs to support tasks undertaken by patients ( n = 14), clinicians ( n = 1), and both ( n = 11). Fourteen studies focused on patients mostly supporting education and self-care [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. One study focused on clinicians, where the CAs were used to educate and increase awareness of the introductory psychology students in mental and physical health [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common chronic condition was diabetes ( n = 5). Two studies were for type 1 [ 29 , 39 ], one study was for type 2 [ 28 ], and one focused on diabetes in general, whether the patients have type 1 or 2 [ 40 ]. One study focused on prediabetes with obesity [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Future studies of diabetes and health management in this population would do well in considering the increasing role and, at times, the necessity of incorporating virtual care models into interventions such as the group intervention presented here, when traditional in-person models may not be possible. Studies have demonstrated the potential role of text messaging and mobile apps in increasing engagement and symptom tracking for individuals with psychosis [ 41 , 42 ] and a growing role for virtual components for enhancing diabetes self-management and support [ 43 , 44 ]; however, to our knowledge, no studies have examined a virtual group intervention for diabetes or a mobile intervention for diabetes tailored for individuals with serious mental illness.…”
Section: Discussionmentioning
confidence: 99%